Membangun Sistem Informasi Kegiatan Dosen Berbasis Webstite Pada Program Studi Teknik Informatika Jurusan Teknik Elektro Politeknik Negeri Pontianak - Hasbi, Muhammad; Firdyanti, Neny; Ramli, Ramli (Jurnal ELIT, 2023)
The Website-Based Lecturer Activity Information System in the Informatics Engineering Study Program, Department of Electrical Engineering, Pontianak State Polytechnic was built to assist students in providing information regarding the schedule of activities carried out related to the main task and additional assignments so as to allow students to make appointments with the lecturers they want to meet. . This information system was built using the Waterfall method with stages consisting of software requirements analysis, software design, program code generation, testing, support and maintenance. The resulting information system can provide information to students in the form of a schedule of activities carried out related to the main task and additional tasks assigned to the lecturer, the presence of the lecturer, and support students to make appointments with the lecturers they want to meet.